Profile of skin diseases in a community of fishermen in the northern coast of the state of São Paulo: the expected and the unusual - Vidal Haddad Junior (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: The fishing colony of the Picinguaba neighborhood is located at the northern end of the coast of the state of São Paulo. It has about 300 residents, of which approximately 100 are professional fishermen. Objectives: This study aimed to identify the main dermatoses of the community in comparison with other populations, and their frequency. Methods: The dermatoses were identified and tabulated for two years, in a prospective study carried out on monthly trips to the fishermen's colony in Picinguaba. Results: One hundred and eighteen patients were attended and followed up, which is equivalent to about 1/3 of the colony's inhabitants. Of these, 43 were children (under the age of 14) and 75 were adolescents and adults. The diseases observed were catalogued according to the age groups. Although most dermatoses in the community were similar with those observed in the general population, some specific cases could be seen, such as folliculitis on the legs of fishermen and an unexpected low frequency of actinic lesions in the colony, as well as dermatitis by aquatic animals. Study Limitations: The limitations were monthly attendance and the spontaneous demand of the patients. Conclusions: The finding of community-specific dermatoses and the low incidence of malignant and pre-malignant tumors associated with sun exposure needs further studies for better clarification.